2005
DOI: 10.1111/j.1747-0765.2005.tb00023.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Chelating Agent Addition on Copper Distribution and Microbial Activity in Soil and Copper Uptake by Brown Mustard (Brassica juncea)

Abstract: A pot culture experiment was conducted using a Cu‐spiked soil to compare the effects of the application of ethylenediamine‐N,N′‐tetraacetate (EDTA) and [S,S]‐ethylenediamine‐N,N′‐disuccinate (EDDS), a biodegradable chelating agent, on the soil Cu distribution, Cu uptake by brown mustard and on the metabolic activity of the soil microorganisms for substrate utilization. Seedlings of brown mustard were planted in the pots fitted with hollow fibers for soil solution suction, and cultivated for 12 weeks. Solutions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…In recent years, several chemical amendments, such as EDTA, have been used to enhance either phytoextraction or phytostabilization process (Barrutia et al 2010). However, chelators may be toxic to plants and to soil microorganisms (Evangelou et al 2007;Ultra et al 2005). A promising alternative is the utilization of plant-microbe interactions to improve the efficiency of phytoremediation, altering the mobility and bioavailability of metals in soils (Glick 2010;Ma et al 2011;Rajkumar et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several chemical amendments, such as EDTA, have been used to enhance either phytoextraction or phytostabilization process (Barrutia et al 2010). However, chelators may be toxic to plants and to soil microorganisms (Evangelou et al 2007;Ultra et al 2005). A promising alternative is the utilization of plant-microbe interactions to improve the efficiency of phytoremediation, altering the mobility and bioavailability of metals in soils (Glick 2010;Ma et al 2011;Rajkumar et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…EDDS, a structural isomer of EDTA, is a promising new alternative synthetic chelant. The [S, S]-isomer is not only readily biodegradable, but also usually performs as well as EDTA (Grčman et al, 2003;Luo, Shen and Li, 2005;Meers et al, 2005;Schowanek et al, 1997;Tandy et al, 2004;Ultra et al, 2005;Vandevivere et al, 2001). EDDS performs better than EDTA at solubilizing Cu and Zn from soils at pH 7 at equimolar ratios of chelating agent to metals (Hauser et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The incubation experiment with long-term heavy metal contaminated soils showed that EDTA amendment seriously affected the microbial biomass C. References on EDTA effects on soil microorganisms differ and some authors report no significant actions (Sapoundjieva et al 2003), in other cases an increase in some microbial parameters was found (Chander and Joergensen 2008). On the other hand, negative effects of EDTA on microbial characteristics were observed (Ultra et al 2005). The course of this experiment showed that EDTA strongly affected the microbial biomass C during the first 24 days of incubation; particularly in the arable soil the microbial biomass contents approached nearly zero values.…”
Section: Resultsmentioning
confidence: 96%
“…The reports of the EDTA effects on microbial activities are various. The addition of EDTA can decrease microbial activities and utilization of substrates (Ultra et al 2005). On the other hand, Chander and Joergensen (2008) showed that the microbial biomass C in long-term contaminated soils tolerated better EDTA amendments than in a low metal soil with zinc.…”
mentioning
confidence: 99%